2019
DOI: 10.1210/clinem/dgz117
|View full text |Cite
|
Sign up to set email alerts
|

Human Endometrial Transcriptome and Progesterone Receptor Cistrome Reveal Important Pathways and Epithelial Regulators

Abstract: Context Poor uterine receptivity is one major factor leading to pregnancy loss and infertility. Understanding the molecular events governing successful implantation is hence critical in combating infertility. Objective To define Progesterone Receptor (PGR)-regulated molecular mechanisms and epithelial roles in receptivity. Design RNA-sequencing and PGR-ChIP-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 94 publications
2
41
1
Order By: Relevance
“…Estrogen regulates multiple STATs, important transcription factors for ISGs, by either enhancing their phosphorylation or DNA-binding activity (40)(41)(42)(43). The genomic-binding site of the progesterone receptor is enriched and overlaps with the binding sites of STAT1, STAT3, and STAT5, suggesting a role for progesterone in ISG activation (44). In contrast, while androgens can increase neutrophil recruitment to inflamed tissues (45-47) they reduce their bactericidal efficiency and ROS synthesis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen regulates multiple STATs, important transcription factors for ISGs, by either enhancing their phosphorylation or DNA-binding activity (40)(41)(42)(43). The genomic-binding site of the progesterone receptor is enriched and overlaps with the binding sites of STAT1, STAT3, and STAT5, suggesting a role for progesterone in ISG activation (44). In contrast, while androgens can increase neutrophil recruitment to inflamed tissues (45-47) they reduce their bactericidal efficiency and ROS synthesis (48).…”
Section: Discussionmentioning
confidence: 99%
“…ER and PR can respectively recognize estrogen and progesterone with specific characteristics. When the receptor binds to the hormone to form a complex, it binds to the chromosome in an activated form, which causes gene activation and promotes, transcribes, and synthesizes new DNA, and then synthesizes new proteins, and promotes the growth and metabolism of endometrial cells through this type of proteins with biological functions (16,17). ER is highly expressed in the endometrium's proliferative stage and low in the ovulation stage; PR is highly expressed in the ovulation stage, while it shows a downward trend in endometrial gland increases in endometrial stromal cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…The implantation is a complex progesterone-dependent event that involves several biological processes that occur in a coordinated fashion in the endometrium, such as cell adhesion, cell growth, differentiation, and signal transduction [ 23 , 35 ]. In a recent study, progesterone has been shown to regulate pathways related to the inflammatory response, xenobiotic metabolism, cell death, epithelial-mesenchymal transition and estrogen response during the window of implantation [ 36 ]. The implantation-associated gene clusters include several genes encoding growth factors, such as TGF α and PlGF .…”
Section: Transcriptional Changes Of Coding Genes In the Endometrium Dmentioning
confidence: 99%